7. Advocating the Poetics of Sound in the Cycle Les Nuits d´Été by Hector Berlioz - Iațeșen Loredana Viorica (Sciendo, 2018)
By consulting monographies, musicological studies, specialty articles about the personality of romantic musician Hector Berlioz and implicitly linked to the relevance of his significant opera, one discovers researchers' constant preoccupation for historical, stylistic, analytical, hermeneutical comments upon aspects related to established scores (the Fantastic, Harold in Italy symphonies, dramatic legend The Damnation of Faust, dramatic symphony Romeo and Juliet, the Requiem, etc.). Out of his compositions, it is remarkable that the cycle Les nuits d´été was rarely approached from a musicological point of view, despite the fact that it is an important opus, which inaugurates the genre of the orchestral lied at the end of the 19th century and the beginning of last century. In this study, we set out to compose as complete as possible an image of this work, both from an analytic-stylistic point of view by stressing the text-sound correspondences and, above all, from the perspective of its reception at a didactic level, by promoting the score in the framework of listening sessions commented upon as part of the discipline of the history of music. In what follows, I shall argue that the cycle of orchestral lieder Les nuits d´été by Hector Berlioz represents a work of equal importance to established opera.